A Characterization for Bishop Equations of Parallel Curves according to Bishop Frame in E3 - Korpinar, Talat; Asil, Vedat; Sariaydin, Muhammed T.; Incesu, Muhsin (Soc Paranaense Matematica, 2015)
In this paper, we study Bishop equations of parallel curves according to Bishop frame in Euclidean 3-space. We obtain a new characterization of parallel curve by using Bishop frame in E-3.
Keywords: Bishop frame; Curves; Euclidean 3-space; Parallel curves